Peanut genes identified during initial phase of Cercosporidium personatum infection - Nobile, Paula Macedo [UNESP]; Lopes, Catalina Romero [UNESP]; Barsalobres-Cavallari, Carla [UNESP]; Quecim, Vera; Coutinho, Luiz L.; Hoshino, Andrea Akemi [UNESP]; Gimenes, Marcos A. [UNESP] (Elsevier B.V., 2008)
Late leaf spot (LLS), caused by the fun.-us Cercosporidium personatum, is one of the most severe diseases in peanut (Arachis hypogaea). The vast majority of commercial cultivars do not exhibit satisfactory levels of resistance to the pathogen, whereas non-commercial genotypes cv. 850 and cv. 909 are resistant to LLS and show symptoms similar to hypersensitive response (HR) lesions. In the present study, we investigated the molecular components of the initial stages of the resistance by gene expression profiling using suppression subtractive hybridization and differential screening of cDNA macroarray techniques. Gene expression analyses have allowed us to identify more than 700 peanut unique expressed sequence taus (EST) involved in several aspects of the early stages of C. personatum pathogenesis, such as components of defense signaling pathways, gene expression regulators, cell cycle controlling genes and components of the biosynthesis of transducer and antimicrobial compounds. The most significantly induced gene corresponds to a novel O'-methyltranferase, suggesting its involvement in the production of local lesions in C. personatum-resistant A. hypogea genotypes. Taken together, our results contribute to elucidate the defense strategies of peanut and provide the framework for the generation of pathogen-resistant peanut cultivars. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: peanut; late leaf spot; host defense response; O'-methyltransferase; suppression subtractive hybridization (SSH)